Teaching English to Food and Beverage Staff: Problems, Challenges, and Possible Solutions - Nurdiana, Nurdiana (Media Antartika Indonesia, 2024)
English is undoubtedly one of the requirements in the hotel and hospitality industry. All hotel staff are required to be able to communicate in English, especially those working in international hotels. This also applies in Indonesia where some international hotels are operating in big cities such as Jakarta. Unfortunately, only a few of the Indonesian hotel staff, including food and beverage employees, have adequate English language competence. Therefore, English training is a must for those working in the hotel industry. The present study, then, was carried out to investigate the problems and challenges of teaching English to food and beverage staff because they communicate with Indonesian and international hotel guests very often, for example, during breakfast, lunch, and, dinner. Careful observation was conducted to look into the problems and challenges, i.e., language problems, trainees’ speaking skills, and in-classroom- participation of each trainee. The findings revealed that most of the food and beverage staff could not communicate in English appropriately and accurately. They were not able to use proper expressions in particular situations with the hotel guests. Meanwhile, the challenges included the use of inappropriate ‘fossilized’ expressions. This implies that there should be solutions to overcome the problems and face the challenges of teaching English to food and beverage staff. Keywords: English, food and beverage staff, language competence